Corrosion Inhibition Efficiency Evaluation and Adsorption Behaviour of Existing and Newly Synthesized Compounds on Mild Steel under CO2 Corrosion Conditions - Beebany, Shakhawan Abdulrahman Omer (Curtin University, 2019)
Corrosion of mild steel under CO2 conditions is a major issue in the oil and gas industry. This thesis provides novel methodology for in-situ characterization of corrosion inhibitor films at carbon steel and under corrosive conditions. The methodology is validated using existing and newly synthesized corrosion inhibitor compounds. This research will significantly benefit corrosion science as it assists in qualification of corrosion inhibitors and can be used directly for improving corrosion mitigation strategies across industries.